Genomic Features of Organ-Specific Metastases in Lung Adenocarcinoma - Feng, Alei; Li, Yanjun; Li, Guangxu; Wang, Yu; Wen, Qiang; Yang, Zhe; Tian, Kaihua; Lv, Hongying; Guo, Lijie; Zhang, Shanshan; Liu, Xiaoyan; Jiang, Da (Frontiers in Oncology, 2022)
Background: The genomic features of cancer cells may confer the metastatic ability of lung adenocarcinoma (LUAD) to metastasize to specific organs. We aimed to identify the differences in genomic alterations between primary LUAD patients with and without metastases, and elucidate the metastatic biology which may help developing biomarker-directed therapies for advanced or metastatic disease. Methods: A retrospective cohort of 497 LUAD patients including 388 primary tumors (PR), 53 bone metastases (MT-bone), 30 liver metastases (MT-liver), and 26 brain metastases (MT-brain) were tested for genomic alterations by a next-generation sequencing assay. Results: The EGFR, TP53, TERT, LRP1B, CDKN2A, ERBB2, ALK, and KMT2C genes had a high frequency of mutations and the mutations were shared by PR and metastases groups. TP53 and EGFR were the most common mutated genes. In comparison to PR, KRAS, STK11, ATM, NPM1, and ROS1 were significantly mutated in MT-brain, and TP53, MYC, RSPO2, CDKN2a, and CDKN2B were significantly mutated in MT-liver. The frequencies of TP53, CDKN2A, MTAP, PRKCI, and APC mutations were higher in MT-bone than that in PR. The ERBB, PI3K-AKT, cell cycle, FGF, and HRD signaling pathways were affected in both PR and metastases, and there are higher frequency mutations in metastases. Moreover, the co-mutations in PR and metastatic patients were respectively analyzed. Additionally, PD-L1 level was obviously related to tumor stage and tumor metastases, and the tumor mutational burden was correlated to clinicopathological features including age, gender, pathological stages, and tumor metastases. FGFR1, KAT6A, MYC, RAD21, TP53, and DAXX were also dramatically correlated to the tumor mutational burden. Conclusion: Metastases are the most devastating stage of tumors and the main cause of cancer-related deaths. Our results provided a clinical-relevant view of the tumor-intrinsic mutational landscape of metastatic LUAD patients.